Peran Ukuran Perusahaan Dalam Memoderasi Pengaruh Tax Minimization, Kualitas Audit Dan Debt Covenant Terhadap Transfer Pricing - Fergy Ardian Syah; Rr. Tjahjaning Poerwati (Journal of Economic, Bussines and Accounting (COSTING), 2023)
The research aims to find out empirical evidence that reduces the research gap, strengthens the model, and analyzes the role of company size in moderating tax minimization, audit quality, and debt covenants on transfer pricing. The sample in this research is manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2019-2021. The sample collection technique used the purposive sampling method and obtainedd 177 samples. The result of this research indicates Tax Minimization and Audit Quality had an effect on Transfer Pricing, and the Debt Covenant had no effect on Transfer Pricing. The Company Size is able to moderate Audit Quality on Transfer Pricing, but company size is not able to moderate tax minimization and debt covenant on transfer pricing. Keywords: Tax Minimization, Audit Quality, Debt Covenant, Company Size and Transfer Pricing